27. TREATMENT OF FEMORAL SHAFT FRACTURES USING INTRAMEDULLARY NAILS WITH LOCKING SCREWS IN POLYTRAUMA PATIENTS AT LE VAN VIET HOSPITAL - THU DUC (Vietnam Journal of Community Medicine, 2024)
Introduction: Femur fractures caused by trauma are a common surgical emergency, occurring across all age groups, most frequently in the working-age population. The causes are usually traffic and occupational accidents. For stable bone fixation, intramedullary nailing with locking screws is one of the viable options.Case presentation: Case 1: A 27-year-old male patient was admitted to the hospital due to a clavicle fracture and a femoral shaft fracture. Seven days post-surgery, the surgical wound had completely healed, and the patient began physical therapy. After three months, the patient showed good results. Case 2: A 27-year-old female patient was admitted to the hospital due to a femoral shaft fracture and a left maxillary sinus posterior wall fracture. Seven days post-surgery, the wound had healed well, and the patient began physical therapy.Discussion: The use of intramedullary nails with locking screws for femoral shaft fractures has been extensively studied and proven effective both internationally and domestically. The presented cases demonstrate the high applicability and success of this method in treating polytrauma patients at primary healthcare facilities.Conclusion: Intramedullary nailing is currently widely used and highly favored by orthopedic trauma surgeons due to its advantages in stability and physiological compatibility.
Keywords: Intramedullary nailing with locking screws, femoral shaft fracture